Retrospective Analysis of Pediatric Hepatoblastoma With Tumor Rupture: Experience From a Single Center - Zhang, Yu-Tong; Zhao, Yu-Fei; Yang, Dian-Fei; Chang, Jian (Frontiers in Pediatrics, 2022)
Purpose Hepatoblastoma (HB) tumor rupture is currently considered as a high-risk factor in some risk-stratification systems. This study aimed to investigate the value of HB tumor rupture in predicting the poor prognosis. Methods The clinical data from children with high-risk HB or HB tumor rupture at our institution from October 2008 to October 2017 were retrospectively reviewed and analyzed. Results Altogether 34 children with high-risk HB or HB tumor rupture were retrospected, including 25 in the high-risk group and 9 in tumor rupture group. The 3-year overall survival (OS) rate in tumor rupture group was significantly higher than that of the high-risk group (100% vs 64%, p=0.0427). In tumor rupture group, 7 (77.8%) out of 9 patients had a hemoglobin level ≤ 8 g/L and 3 of them (33.3%) had ≤ 6 g/L at the time of diagnosis. Peritoneal perfusion with interleukin-2 was implemented for each patient. At the end of the treatment, 7 (77.8%) of 9 patients achieved complete response (CR). No patient died at the last follow-up. Conclusions HB tumor rupture might not be predictive of poor prognosis with the risk of peritoneal dissemination/relapse, in which peritoneal perfusion with interleukin-2 could play a role.